Spatial heterogeneity of macrofauna at northern California methane seeps: Influence of sulfide concentration and fluid flow - Levin, L. A.; Ziebis, W.; Mendoza, G. F.; Growney, V. A.; Tryon, M. D.; Brown, K. M.; Mahn, C.; Gieskes, J. M.; Rathburn, A. E. (Marine Ecology Progress Series, 2003)
Relationships among fluid flow, sulfide concentration, sulfur bacteria and macrofaunal assemblages were examined at methane seeps on the northern California margin, near the mouth of the Eel River (512 to 525 m). Over a 6 mo period, sediments covered with microbial mats exhibited significant but variable outflow of altered fluids, with no flow reversals. This fluid flow was associated with high porewater sulfide concentrations (up to 20 mM) and almost no oxygen penetration of sediments (<0.1 mm). Vesicomya pacifica (clam) bed and non-seep sediments exhibited little net fluid outflow and similar oxygen penetration (3 and 4 mm, respectively); however, sulfide concentrations were higher in subsurface clam-bed sediments (up to 2 mM) than in non-seep sediments (<200 muM). Macrofaunal densities did not differ among the 3 habitats (13 800 to 16 800 ind. m-2; >300 mum), but biomass and diversity (no. species per core, E(S100), H') were lower and composition varied in the sulfidic microbial mat sediments relative to clam-bed and non-seep sediments. The community in microbial mat-covered sediments consisted largely (82%) of 6 species in the polychaete family Dorvilleidae, whereas the clam-bed and non-seep microhabitats supported a mixture of annelids, peracarid crustaceans, nemerteans, and mollusks. Vertical microprofiling of sulfide in animal cores indicated that most taxa avoid H2S concentrations >1 mM. However, sulfide-oxidizing filamentous bacteria, dorvilleid polychaetes and bivalves (mainly V. pacifica) exhibited highest densities at sulfide concentrations of 1 to 5 mM sulfide. Horizontal and vertical patterns of sulfide availability have a strong influence on the fine-scale distribution, structure and composition of macrofaunal assemblages inhabiting methane seeps and must be accounted for when characterizing the microbiology and ecology of seep habitats.
NeMys doc_id: 11061